Neuraminidase antigenic drift of H3N2 clade 3c.2a viruses alters virus replication, enzymatic activity and inhibitory antibody binding - Powell, Harrison; Pekosz, Andrew (PLoS pathogens, 2020)
In the 2014-2015 influenza season a novel neuraminidase (NA) genotype was detected in global human influenza A surveillance. This novel genotype encoded an N-linked glycosylation site at position 245-247 in the NA protein from clade 3c.2a H3N2 viruses. In the years following the 2014-2015 season, this novel NA glycosylation genotype quickly dominated the human H3N2 population of viruses. To assess the effect this novel N-linked glycan has on virus fitness and antibody binding, recombinant viruses with (NA Gly+) or without (NA Gly-) the 245 NA glycan were created. Viruses with the 245 NA Gly+ genotype grew to a significantly lower infectious virus titer on primary, differentiated human nasal epithelial cells (hNEC) compared to viruses with the 245 NA Gly- genotype, but growth was similar on immortalized cells. The 245 NA Gly+ blocked human and rabbit monoclonal antibodies that target the enzymatic site from binding to their epitope. Additionally, viruses with the 245 NA Gly+ genotype had significantly lower enzymatic activity compared to viruses with the 245 NA Gly- genotype. Human monoclonal antibodies that target residues near the 245 NA glycan were less effective at inhibiting NA enzymatic activity and virus replication of viruses encoding an NA Gly+ protein compared to ones encoding NA Gly- protein. Additionally, a recombinant H6N2 virus with the 245 NA Gly+ protein was more resistant to enzymatic inhibition from convalescent serum from H3N2-infected humans compared to viruses with the 245 NA Gly- genotype. Finally, the 245 NA Gly+ protected from NA antibody mediated virus neutralization. These results suggest that while the 245 NA Gly+ decreases virus replication in hNECs and decreases enzymatic activity, the 245 NA glycan blocks the binding of monoclonal and human serum NA specific antibodies that would otherwise inhibit enzymatic activity and virus replication.